Fisher information in ranked set sampling from the simple linear regression model - Wang, Shuo; Chen, Wangxue; Yang, Rui (Communications in statistics. Simulation and computation, 2024)
Fisher information is a fundamental concept of statistical inference and plays an important role in many areas of statistical analysis. In this paper, we obtain explicit expressions for the Fisher information matrix in ranked set sampling (RSS) from the simple linear regression model with replicated observations. It has been shown to be the sum of two matrices, one of which is the Fisher information matrix based on simple random sampling (SRS). The numerical results show that RSS provides more information than SRS when the same sample size is used.